Mathematical models to predict repair and maintenance cost for 2WD tractors in the mechanized rainfed areas, eastern Sudan - Yousif, Lotfie A. (Gezira Journal of Agricultural Science, 2016)
Many tractor makes are working in the mechanized rainfed areas of eastern Sudan. Most of them are two-wheel drive (2WD) tractors. However, information concerning their repair and maintenance (R and M) costs are inadequate. Moreover, depending on information on R and M costs from other farming systems or countries is unrealistic. Four tractors were studied, which were Massy Ferguson (MF-290), Ford (FD-6610), Belarus (BL-800) and New Holland (TT-75). The objectives were to develop mathematical models to estimate tractors' annual R and M costs, to rank the studied tractors according to their predicted R and M costs and to compare estimations of the general model developed from this study with models developed elsewhere. Data on purchase price, annual working hours, fuel consumption, R and M costs, labor wage and oil costs were collected. The regression and F test analyses methods were used. Results revealed that the power function Y= aX b can be used to estimate tractor R and M costs; where Y is R and M costs as percent of purchase price and X is annual working hours. The annual working hours had very highly significant (P= 0.001) effect on R and M costs. The values of coefficient of determination (R 2 ) were above 0.95 for all tractors and their general model. The developed models for all tractors were arranged in ascending order according to their predicted R and M costs as follows; Y = 0.05 (X/100) 1.3 for TT-75,   Y = 0.04(X/100) 1.4 for BL-800, Y= 0.03 (X/100) 1.7 for MF-290 and Y = 0.05 (X/100) 1.5 for FD-6610. The general model from this study was   Y = (0.041 (X/100) 1.43 ). This general model predicted lower R and M costs compared to the models suggested for irrigated schemes of Sudan and some other countries. It is advised that each specific area and country must develop its own mathematical model.